Characterization of Bragg grating pressure sensor using finite element analysis theory and experimental results (2010)
M.Ing. === Optical fibre Bragg gratings are a periodic variation of the refractive index in the core of an optical fibre andmay be formed by exposure to intense UV laser light under specific conditions. Light at a certain wavelength, called the Bragg wavelength, is reflected back when illuminating the grating with a light source. Bragg gratings can relatively easily be employed as strain and temperature sensors, but have small sensitivity for pressure. Special transducers are required to increase the sensitivity. A pressure sensor was manufactured by coating a fibre Bragg grating with a polymer. The polymer coating converts transverse pressure into longitudinal strain through the Poisson effect inside the polymer coating. This thesis investigates the sensitivity of themanufactured Bragg grating pressure sensor, by using the method of finite element analysis. An account of the experimental setup, whereby the Bragg grating is written with a frequency tripled Nd:YAG laser, is given. The process whereby the fibre is coated with the polymer is described. The sensor is characterized through experimental results and a comparison is made between theoretical and experimental results. Uses for this sensor and ways with which the sensitivity may be increased are suggested as future work.